the ANALISIS PENGUKURAN PRODUKTIVITAS BETON READY MIX DENGAN METODE OMAX (OBJECTIVE MATRIX) PADA PT PIONIRBETON INDUSTRI: bahasa indonesia - AJI, PRASETYO; Andung Jati Nugroho (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2022)
PT Pionerbeton Indiustri is one of the companies engaged in the production of ready mix concrete, which is a subsidiary of PT Indocement Tunggal Perkasa, Tbk for casting projects located in JL. Ahmad yani (South Ringroad), Padukuhan Modalan RT 02, Banguntapan Village, Banguntapan District, Bantul Regency DIY. The method used in the study was to use the OMAX (Objective Matrix) method. This research was conducted for 12 months, namely January-December 2021. This research was conducted using the OMEX (Objecktive Matrix) method, so that in processing the data is carried out by following the steps of OMAX (Objecktive Matrix). The purpose of this study is to determine the ratios that most affect the rise and fall of productivity levels with the Objecktive Matrix method. Based on calculations using the Objecktive Matrix method, it shows that the productivity data of PT Pionirbeton Industri has a low value in September material, which is 471,134,817 due to the late supply of raw materials which results in decreased productivity in September.